Efektivitas Terapi Bermain Play Dough dalam Meningkatkan Kemampuan Motorik Halus Anak Hambatan Intelektual Sedang - Fitri, Herlindah; Khoeriah, N. Dede (Papanda Publisher, 2025)
The development of basic skills in children with moderate intellectual disabilities in special schools is often hindered by insufficient targeted therapeutic interventions to enhance their fine motor abilities. Play dough therapy is recognized as a valuable tool for training hand and finger movements, yet limited research has demonstrated its effectiveness specifically for children with moderate intellectual disabilities in special elementary schools (SDLB). This study aims to determine the effectiveness of play therapy using play dough media in improving fine motor skills among children with moderate intellectual disabilities in grade 1 SDLB at SLB Negeri Pahlawan Indramayu. The research employed a quantitative approach utilizing a single-subject experimental design (Single Subject Research) with an A-B-A model. The participant was a 7-year-old girl diagnosed with moderate intellectual disability. Data collection methods included systematic observation and fine motor skills performance assessments. The intervention consisted of eight structured sessions focusing on manipulative activities using play dough, including squeezing, pinching, rolling, and shaping exercises. Analysis revealed significant improvement in fine motor skills, with performance increasing from an initial baseline average of 54% to 94% in the final baseline phase, representing a 40% improvement. These findings demonstrate that play therapy with play dough constitutes an effective intervention for enhancing fine motor skills in children with moderate intellectual disabilities. The therapy also positively impacted the child's concentration levels, independence, and perseverance during learning activities. Additionally, the structured play approach facilitated better engagement and motivation throughout the therapeutic process. Therefore, play dough therapy is recommended as an alternative educational strategy in special schools for children with special needs, particularly those requiring fine motor skill development interventions.